Large hole artifacts in the formalin-fixed brain from a drowning case with head lacerations: A forensic autopsy case - Tadashi Hosoya; Kazuki Harada; Jun Kanetake (Forensic Science International: Reports)
A man in his forties with two lacerations in the occiput was found in a river. A forensic autopsy revealed that the cause of death was drowning, and the blood ethanol concentration was 1.5 mg/mL. The whole brain was fixed with formalin for 15 days using the standard immersion method to evaluate this. The fixed brains showed large holes in the deep white matter as artifacts. Research suggests that formalin-fixed brains from drowning cases tend to have “Swiss cheese-like” holes in the deep white matter. However, this study is the first to report a case that focuses on large holes as artifacts. The holes in the fixed brain may have been caused by postmortem invasion of freshwater indigenous bacteria and gas formation.